Low subjective socioeconomic status alters taste-based perceptual sensitivity to the energy density of beverages - Lim, Elizabeth X. (2021)
Lower socioeconomic status (SES) is associated with increased consumption of energy-dense foods and sugar-sweetened beverages. Recent findings suggest that the mere perception of having lower subjective SES (SSES) compared to others was sufficient to elicit heightened preferences and consumption of higher energy foods and meals. This increased drive for energy intake associated with low SSES may be accompanied by heightened perceptual sensitivity to the presence of energy in foods, which may aid discrimination and selection of energy-dense foods. The present study tested this prediction by investigating whether acute experiences of low SSES may produce subsequent shifts in perceptual sensitivity to the energy density of beverages. Participants performed two taste tests on 6 iced tea beverages that varied in energy density prior to (at baseline) and after an experimental SSES manipulation. There were no differences in general frequency of ice tea consumption across the SSES conditions. Results revealed that participants were better at perceiving beverages that were higher in energy to be more energy dense following the low SSES manipulation (compared to baseline evaluations). By contrast, participants in the high SSES and neutral control conditions exhibited no overall consistent change in sensitivity to perceived energy density across the beverages following the manipulation. Additionally, no effects of SSES manipulation were observed for rated palatability of the beverages. These findings demonstrate that subjective experiences of having inadequate socioeconomic resources may produce taste-based perceptual shifts that increase sensitivity to the presence of energy in foods, potentially through heightened attentiveness to or expectations of sensory characteristics that signal energy (i.e., sweetness, texture). Such perceptual shifts may have been adaptive for facilitating the discrimination and selection of energy-dense foods in the face of resource insecurity. Importantly, this study suggests that merely perceiving a socioeconomic disadvantage may enhance identification and consumption of energy-dense foods and beverages, which may represent a psychosocial process that contributes to socioeconomic disparities in consumption of energy dense foods, and may be operational via heightened perceptual sensitivity to sensory cues associated with the presence of energy in the consumed food.